(untitled) (American Journal of Islam and Society, 1991)
The paradigm shifts from the 1950s to the 1980s in political science are best explained with reference to the encounter with the Other, an encounter which has three stages: first, the self-confident representation of the Other which is characteristic of modernity; second, the fear of and desire to control the Other which is characteristic of the end of modernity; and third, the hyperrealization and trivialization of the Other which is characteristic of postmodernity. This encounter with the Other takes place within a larger discourse context or episteme. The epistemic shifts, then, must also be considered. Paradigm Shift Foucault’s concept of archaeology includes the idea that scientific systems are valid within their own contexts. Thus each piece of historical data must be judged and assessed in its own stratum or context. In a less sophisticated fashion, Kuhn has taken this idea of historical context and cultural relativism and come up with a theory of scientific revolution. Kuhn correctly identifies the science textbook genre as the received history of normal science, a genre which incorporates the myth of the steady cumulative process of science. The textbook mythology traces the history of great white men and great experiments as they contributed their energies to the irresistible march of scientific progress. Kuhn demonstrates that Aristotelian dynamics or caloric thermodynamics are in fact internally systematic and scientific and are therefore just as valid as contemporary dynamics or thermodynamics. In reference to their “fit” with nature, an earth-centered astronomy is just as valid as a suncentered astronomy. What happens is that when the questions change, and questions are asked which strain an earth-centered astronomy, a paradigm ...